A literature review of citizen science for hydrological monitoring - with specific focus on lessons learned in developing countries - Kwakye, E.; Barron, J.; Adusei-Gyamfi, J.; Atampugre, Gerald; Tilahun, Seifu A. (International Water Management Institute (IWMI). CGIAR Initiative on West and Central African Food Systems Transformation, 2024)
Citizen science has emerged as a significant approach to engage the public in scientific research, data collection, and environmental monitoring, around hydrology. This meta-review examines the scientific literature on the involvement of citizens, recruitment and training, spatiotemporal distribution of cases, methodologies or approaches, the precision of citizen science data with controlled measurements, data transfer and accessibility, usage of citizen science data, and who uses the data and equipment used in citizen science projects for hydrological monitoring. The systematic review identified 14 review papers published since 2015, summarising 492 case studies, with a concentration of evidence based on regions in high, upper, and low-middle-income countries.